METHODOLOGY OF ANALYSIS AND EVALUATION OF FINANCIAL CONDITION OF ENTERPRISES OF MACHINE-BUILDING INDUSTRY - O. Diakonova; N. Samoiylova (Вестник университета)
In this article, we consider methods for analyzing the financial state of various authors. Based on the reviewed methods, an analysis was made and an assessment of the financial condition of the machine-building industry enterprise - PJSC «Kamaz». Based on the results of the analysis, conclusions and recommendations for improving the financial condition of PJSC «Kamaz» were formulated.